Revegetation of Critical Land with Gaharu (Aquilaria malaccensis) under Various Ameliorants Application - Yuwono, Slamet Budi; Alawiyah, Alawiyah; Riniarti, Melya; Dermiyati, Dermiyati (JOURNAL OF TROPICAL SOILS, 2021)
Rehabilitation of post-mining limestone soils is often a challenge due to a lack of nutrients and poor soil humus. The research aims to study the effect of various ameliorants on soil chemical properties, growth, and P uptake of gaharu plant (Aquilaria malaccensis) in post-mining limestone soil for revegetation of critical land. The research was conducted in a Completely Randomized Design with three replications. The treatments were P0 (Control, without ameliorant); P1 (Humic Acid, HA, 4 kg ha-1 ); P2 (Phosphate Rocks, PR, 350 kg ha-1 ); P3 (Vesicular Arbuscular Mycorrhizal Fungi, AMF, 500 spores plant-1 ); P4 (HA+AMF); P5 (PR+AMF); and P6 (HA+PR+AMF). Data were analyzed using ANOVA at 95% confidence level and continued with the LSD test. The use of various types of ameliorants (HA, RP, and AMF) significantly increased root length, root volume, wet and dry weight of roots, shoot wet and dry weight, and P uptake of gaharu tree. The best ameliorant in increasing gaharu tree growth was AMF (P3) treatment, and AMF combined with HA (P4) treatment. Thus, for revegetation of critical land, especially post-mining limestone land, using gaharu tree requires HA and AMF inoculation.